1998
DOI: 10.1523/jneurosci.18-23-10128.1998
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Application of Melanocortin Receptor Ligands Produces Long-Lasting Effects on Feeding and Body Weight

Abstract: Recent evidence suggests that the central melanocortin (MC) system is a prominent contributor to food intake and body weight control. MC receptor (MC-R) populations in the arcuate and paraventricular nuclei are considered probable sites of action mediating the orexigenic effects of systemically or intracerebroventricularly administered ligands. Yet, the highest MC4-R density in the brain is found in the dorsal motor nucleus of the vagus nerve, situated subjacent to the commissural nucleus of the solitary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
139
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 260 publications
(154 citation statements)
references
References 39 publications
(58 reference statements)
12
139
0
2
Order By: Relevance
“…We undertook to explore the functional relevance of brainstem MC-R via 4th-icv and brainstem parenchymal injection of MTII, a MC3/4-R agonist (see also 25), and of SHU-9119. Each treatment yielded dose-related short-and long-term intake effects that were not distinguishable from those obtained from lateral icv delivery (70). On face value, the finding is consistent with the suggestion that the lateral and 4th-icv injections stimulate different subsets of MC-R that independently can give rise to what is essentially the same response.…”
Section: Melancortinsupporting
confidence: 82%
See 1 more Smart Citation
“…We undertook to explore the functional relevance of brainstem MC-R via 4th-icv and brainstem parenchymal injection of MTII, a MC3/4-R agonist (see also 25), and of SHU-9119. Each treatment yielded dose-related short-and long-term intake effects that were not distinguishable from those obtained from lateral icv delivery (70). On face value, the finding is consistent with the suggestion that the lateral and 4th-icv injections stimulate different subsets of MC-R that independently can give rise to what is essentially the same response.…”
Section: Melancortinsupporting
confidence: 82%
“…Consistent with this perspective: (i) leptin receptors are expressed on arcuate hypothalamic neurons that also express POMC or AgRP, (ii) leptin treatment increases expression of POMC mRNA and decreases AgRP mRNA, and (iii) the synthetic melanocortin 3/4 receptor (MC3/4-R) antagonist, SHU-9119, reverses the short-term intake inhibition that follows icv application of leptin (123,164,201). Direct agonist stimulation of MC3/4-R via icv treatment produces a short-latency, dose-related inhibition of food intake that lasts for 24 h, while antagonist treatment yields a robust hyperphagia that persists for several days after a single application (70,83).…”
Section: Melancortinmentioning
confidence: 99%
“…Immunocytochemical, in situ hybridization, and binding studies have identified both MC3R and MC4R in the DVC, and their role in food satiation has been suggested by behavioral studies (Joseph et al, 1985;Palkovits et al, 1987;Bronstein et al, 1992;Grill et al, 1998;Williams et al, 2000;Kishi et al, 2003;Liu et al, 2003;Fan et al, 2004;Zheng et al, 2005). Although our pharmacological experiments could not differentiate between MC3R and MC4R, our reverse transcription-PCR results reveal that mRNA for only MC4R is present in the nodose ganglia and in the dorsal caudal brainstem area, suggesting the effects of melanocortin agonists occur via MC4R only.…”
Section: Mc4r Modulation Of Glutamatergic Synaptic Transmission Is Mamentioning
confidence: 44%
“…Activation of brainstem melanocortin receptors inhibits food intake potently with a concomitant increase in energy expenditure (Grill et al, 1998;Williams et al, 2000;Fan et al, 2004;Zheng et al, 2005). Here, we provided a possible cellular mechanism (i.e., a melanocortin-mediated increase in glutamate transmission to NTS neurons).…”
Section: Implications For the Control Of Food Intakementioning
confidence: 88%
See 1 more Smart Citation